Plant-based functional foods from Borneo - Oliver Dean John; Noumie Surugau; Jibrail Kansedo; Sunil K. Panchal; Lindsay Brown (MDPI, 2025)
Borneo, the third-largest island in the world, is shared between Malaysia (Sabah and Sarawak), Indonesia (Kalimantan) and Brunei. As a biodiversity hotspot, it is home to about 15,000 flowering plants and 3000 tree species, of which many are endemic to the region. Locally derived plant-based foods are gaining popularity due to their lower environmental impact, contribution to food sustainability and health benefits. The local fruits and vegetables of Borneo have been used traditionally by the indigenous community for medicinal purposes. This community knowledge can provide a valuable guide to their potential for use as functional foods. This review explores the contemporary foods from Borneo, including fruit, vegetables, seaweeds and plant-derived food products that are locally consumed. The findings show that the unique tropical food groups have a wide diversity of phytochemical compositions that possess a wide array of biological activities including anti-inflammatory, antioxidant, anti-microbial, anti-proliferative, anti-fungal, wound healing and expectorant properties. The wide range of plant-based foods in Borneo deserves further development for wider applications as functional foods.